2022
DOI: 10.1123/ijspp.2021-0543
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown: A Global Study Investigating the Effect of Athletes’ Sport Classification and Sex on Training Practices

Abstract: Purpose: To investigate differences in athletes’ knowledge, beliefs, and training practices during COVID-19 lockdowns with reference to sport classification and sex. This work extends an initial descriptive evaluation focusing on athlete classification. Methods: Athletes (12,526; 66% male; 142 countries) completed an online survey (May–July 2020) assessing knowledge, beliefs, and practices toward training. Sports were classified as team sports (45%), endurance (20%), power/technical (10%), combat (9%), aquatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 35 publications
4
37
1
Order By: Relevance
“…In regard to purpose of training, females demonstrated a greater tendency for maintenance of muscle balance as a training priority than males. This result was not observed in a global study (Washif, et al, 2022c) that found more female athletes prioritizing fitness/health maintenance, abdominal strength, and flexibility. These data indicate an influence of country-specific related to training priority when considering sex difference.…”
Section: Lockdown-enforced Changes In Training Practices According To...contrasting
confidence: 83%
See 4 more Smart Citations
“…In regard to purpose of training, females demonstrated a greater tendency for maintenance of muscle balance as a training priority than males. This result was not observed in a global study (Washif, et al, 2022c) that found more female athletes prioritizing fitness/health maintenance, abdominal strength, and flexibility. These data indicate an influence of country-specific related to training priority when considering sex difference.…”
Section: Lockdown-enforced Changes In Training Practices According To...contrasting
confidence: 83%
“…Males and females demonstrated reduced training frequency and duration in the Philippines. These findings somehow support the global trend during COVID-19 lockdown (Washif, et al, 2022c). In regard to purpose of training, females demonstrated a greater tendency for maintenance of muscle balance as a training priority than males.…”
Section: Lockdown-enforced Changes In Training Practices According To...supporting
confidence: 80%
See 3 more Smart Citations